Exploring the Potentials of English Teachers’ Professional Identity Development in Algerian Higher Education Settings - Boudjelal, Mustapha (Technium Social Sciences Journal, 2022)
This article attempts to shed light on English teachers’ professional identity development in Algerian higher education as it scrutinises certain interior and exterior factors that influence and shape the debated process. To explore this aim, both teachers’ perceptions of the targeted concept and the contexts that shape and influence the outlined construct were investigated via two main research instruments: a questionnaire and a structured interview administered to 11 English language teachers from the University of Mostaganem. The first research instrument was used to gauge teachers’ understandings and perceptions of their identities which play a cardinal role in enacting professional identities. Howbeit, the second one sought to explore the status quo of professional development in Algerian universities. The analysis of the findings revealed that teachers show a readiness and an eagerness to embrace professional identities development; however, these aspirations are obstructed by certain misconceptions about professional identity development and certain working conditions which do not help much in developing professional identities. Given the provided suggestions by the teachers, this study underscores the prioritisation of developing teachers’ professional identities by means of reinforcing both the interior and the exterior factors which occupy a central role in the very construal of the debated construct.